The missing chums - Dixon, Franklin W. (New York : Grosset & Dunlap, an imprint of Penguin Random House, 1990)
A series of bizarre events in their home town lead the Hardy Boys on a trail of robbers and kidnappers.
Exciting assignment -- Evening of mystery -- Faces in the fog -- Daring getaway -- Dancing gorillas -- Perilous slide -- Dangerous beachcombing -- Postcard puzzle -- Old salt's story -- Narrow escape -- Midnight caller -- Desolate island -- Threatening figure -- Signal three -- Outwitting a suspect -- Skeleton symbol -- Hermit's hideout -- Hidden watchers -- Rocky prison -- Ambushing the enemy.
Grades 4-7.
670L
Accelerated Reader
Accelerated Reader AR
edited hb 2015-06-16
Keywords: Detective and mystery stories -- Juvenile literature; Missing persons -- Juvenile fiction; Kidnapping -- Juvenile fiction; Friendship -- Juvenile fiction; Brothers -- Juvenile fiction; Hardy Boys (Fictitious characters) -- Juvenile fiction; Hardy, Joe (Fictitious character) -- Juvenile fiction; Hardy, Frank (Fictitious character) -- Juvenile fiction; Mystery and detective stories. -- Fiction; Missing persons -- Fiction; Kidnapping -- Fiction; Friendship -- Fiction; Brothers -- Fiction; Hardy Boys (Fictitious characters) -- Fiction; Hardy, Joe (Fictitious character) -- Fiction; Hardy, Frank (Fictitious character) -- Fiction; Fiction; Detective and mystery fiction